Resistance to Economic Oligarchy in the Al-Quran through the Lens of Tafsir Nuzuli - Rifqa, Zakiyan; Shidqon, Alfan; Tumewu, Noufal P. (TAFSE: Journal of Qur'anic Studies, 2023)
This article aims to examine the Quran's resistance to economic oligarchy by referencing the interpretations of Surah Al-Humazah and Al-Hashr: 7. Employing the tafsir Nuzuli approach from the perspective of Muhammad Abid al-Jabiri, the article delves into two main issues: Firstly, the review of the tafsir Nuzuli concerning economic principles in Surah Al-Humazah and al-Hashr verse 7. Secondly, the correlation between these verses and their contextualization in relation to economic oligarchy. The study adopts a literature review using a descriptive-analytical method. Based on an analysis of interpretation aspects, sabab nuzul, and the historical context of pre-Islamic Arabia, the study concludes that the verses articulate the Quran's opposition to economic oligarchy. The interpretation of Surah Al-Humazah condemns the propaganda of economic oligarchy perpetrators, specifically a group of pagan Quraisy elites. The interpretation of al-Hashr verse 7 reveals the wealth distribution policy implemented during the Prophet's leadership in Medina based on maslahah, ensuring the avoidance of concentrating wealth exclusively among a select few affluent individuals. The sabab nuzul of these verses, associated with the conditions of pre-Islamic Arabia, elucidates the Quranic vision of economic justice, allowing for its contextualization in the present era.